2020
DOI: 10.1016/j.bja.2020.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Continuous noninvasive pulse wave analysis using finger cuff technologies for arterial blood pressure and cardiac output monitoring in perioperative and intensive care medicine: a systematic review and meta-analysis

Abstract: Background: Finger cuff technologies allow continuous noninvasive arterial blood pressure (AP) and cardiac output/index (CO/CI) monitoring. Methods: We performed a meta-analysis of studies comparing finger cuff-derived AP and CO/CI measurements with invasive measurements in surgical or critically ill patients. We calculated overall random effects model-derived pooled estimates of the mean of the differences and of the percentage error (PE; CO/CI studies) with 95%-confidence intervals (95%-CI), pooled 95%-limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 73 publications
5
79
2
2
Order By: Relevance
“…Several previous studies compared ccNexfin/ClearSight blood pressure measurements with intraarterial reference blood pressure measurements using an arterial catheter in mixed patient populations not explicitly focusing on obese patients. 14 Between these studies, there is substantial variability regarding the blood pressure measurement performance of the finger cuff technology, with several studies demonstrating interchangeability between blood pressure values obtained by either method, but others showing poor agreement. 14 However, data on the measurement performance of finger cuff technologies in severely obese patients are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies compared ccNexfin/ClearSight blood pressure measurements with intraarterial reference blood pressure measurements using an arterial catheter in mixed patient populations not explicitly focusing on obese patients. 14 Between these studies, there is substantial variability regarding the blood pressure measurement performance of the finger cuff technology, with several studies demonstrating interchangeability between blood pressure values obtained by either method, but others showing poor agreement. 14 However, data on the measurement performance of finger cuff technologies in severely obese patients are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…14 Between these studies, there is substantial variability regarding the blood pressure measurement performance of the finger cuff technology, with several studies demonstrating interchangeability between blood pressure values obtained by either method, but others showing poor agreement. 14 However, data on the measurement performance of finger cuff technologies in severely obese patients are scarce. A study in 35 severely obese patients having bariatric surgery showed that ClearSight blood pressure measurements showed good agreement with intraarterial blood pressure measurements for mean arterial pressure and diastolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…As none of our volunteers had peripheral vasoconstriction, the volume clamp method can provide reliable estimates of changing stroke volume [ 31 ]. While we have shown that changing SV, measured by volume clamp, is also tracked by Doppler of the descending aorta and bioreactance technologies [ 28 ], volume clamp is an indirect measure and may not be valid in surgical patients and the critically ill as compared to thermodilution [ 39 , 40 ]. The advantages of the volume clamp method are that it is non-invasive and non-operator dependent.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, innovative finger-cuff technologies became available that allow continuous recording of the arterial blood pressure waveform and PPV calculation in a non-invasive manner [5][6][7][8][9][10]. The CNAP system (CNAP Monitor 500; CNSystems Medizintechnik, Graz, Austria) is one commercially available finger-cuff system and has been validated for arterial blood pressure and cardiac output measurements [11]. Using a proprietary algorithm, the CNAP system also automatically calculates PPV (PPV CNAP ).…”
Section: Introductionmentioning
confidence: 99%